ダイ42ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 2001 - 田口, 雄二; タグチ, ユウジ; 加藤, 裕規; カトウ, ユウキ; 肆矢, 朗久; ヨツヤ, アキヒサ; 坪井, 一寛; ツボイ, カズヒロ; 池田, 友紀子; イケダ, ユキコ; Taguchi, Yuji; Kato, Yuki; et al. (2006)
P(論文) この報告は,第42次南極地域観測隊気象部門が,2001年2月1日から2002年1月31日まで昭和基地において行った気象観測結果をまとめたものである.観測方法,測器,統計方法等は,第41次隊とほぼ同様である. 越冬期間中,特記される気象現象として,次のものが挙げられる.1) 高層気象観測において,9月から11月にかけて,成層圏下部の気温が30年平均値に比べ著しく低かった.2) オゾン全量観測では,大きなオゾン減少を観測し,9月と11月の月平均オゾン全量値は観測開始以来の最低値となった.3) エアロゾルゾンデ観測において,オゾンホール出現前の6月に極域成層圏雲(PSCs)が形成されていることが観測された. This report presents results of meteorological observations performed by the 42nd Japanese Antarctic Research Expedition from February 1, 2001 through January 31, 2002 at Syowa Station. Instruments and means of compiling statistics were similar to those used on the 41st Expedition. Remarkable weather phenomena during the wintering period are as follows.1) Anomalously low temperature was observed in the lower stratosphere from September to November.2) Severe ozone depletion was found by total ozone observation. The lowest monthly means of total ozone since 1966 were recorded in September and November.3) Polar stratospheric clouds (PSCs) were observed by using aerosol sondes in June, before ozone hole appearance. departmental bulletin paper